A study on credit evaluation of power consumer based on the topsis and AHP method - Nongkang, Jumriani (2013)
The credit evaluation of power consumer is very important for the power company in the market operation. Inability to pay electricity charges due has always been a fundamental problem in electricity markets. This paper discusses credit evaluation of power consumer concept and constructs evaluation index system for credit power consumer then describes the theories and procedures of TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) evaluation method and AHP (Analytic Hierarchy Process) method. “5C” which is often made use of by department of credit management in current credit evaluation, character, capacity, capital, collateral and condition, take as the basic to construct the consumer credit index system. Consumer credit evaluation divide power consumer into different credit rating. Finally, this paper takes ten customers for example data, using TOPSIS and AHP method to evaluate the credit power consumer. The method of TOPSIS, based on the original data matrix after their normalization, is to find out the optimal plan and the worst plan among the limited plans, and then calculate the differences between the various evaluation targets and the optimal and worst plans so as to obtain the relative closeness degree between them, which then will b used to judge whether they are good or bad ones. AHP uses simple pairwise comparisons to determine weights.